Epistemologi Ilmu Menurut Paradigma Wahdatul Ulum - Salamuddin Salamuddin; Nur Helmi; Nuraisyah Sitorus; Sopan Sofian (Jurnal Ilmiah Wahana Pendidikan, 2023)
The secular understanding developed by the West is a separation between science and religion, so that between science and religion there is no relationship and there is a dichotomy between the two. Where in science, religion cannot influence and is not considered relevant between religion and science, so science and religion cannot go hand in hand. Secular understanding is an erroneous understanding in Islam so it needs to be corrected by carrying out scientific integration or can be called wahdatul ulum. The purpose of this study is to describe how science in the view of wahdatul ulum. The method used in this research is a qualitative approach. With this type of library study research or what can be called a literature study, namely research that limits research activities to materials contained in the library without conducting research in the field. The understanding of wahdatul ulum is an understanding that unites knowledge from two different sources, namely religious knowledge and science into an interconnected unit, then the unification of qawliyah verses originating from the Koran with kawniyah verses originating from the universe becomes a unity, namely a knowledge that both come from Allah SWT. So that a new paradigm is formed in the scientific field that combines religious knowledge with science.